2012
DOI: 10.1007/s10295-011-1055-z
|View full text |Cite
|
Sign up to set email alerts
|

Alginate production and alg8 gene expression by Azotobacter vinelandii in continuous cultures

Abstract: Alginates are polysaccharides that are used as thickening agents, stabilizers, and emulsifiers in various industries. These biopolymers are produced by fermentation with a limited understanding of the processes occurring at the cellular level. The objective of this study was to evaluate the effects of agitation rate and inlet sucrose concentrations (ISC) on alginate production and the expression of the genes encoding for alginate-lyases (algL) and the catalytic subunit of the alginate polymerase complex (alg8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 28 publications
10
34
0
Order By: Relevance
“…In disagreement with these results, Díaz-Barrera et al . [10] reported that in chemostat cultures fed sucrose (15 g l −1 ), a percentage of carbon (20 and 35%) was diverted to acetate and malate, which were released into the culture medium. This different behavior could be attributed to the non-nitrogen-fixation conditions used by Díaz-Barrera et al .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In disagreement with these results, Díaz-Barrera et al . [10] reported that in chemostat cultures fed sucrose (15 g l −1 ), a percentage of carbon (20 and 35%) was diverted to acetate and malate, which were released into the culture medium. This different behavior could be attributed to the non-nitrogen-fixation conditions used by Díaz-Barrera et al .…”
Section: Resultsmentioning
confidence: 99%
“…This different behavior could be attributed to the non-nitrogen-fixation conditions used by Díaz-Barrera et al . [10], compared to the nitrogen-fixing conditions used in this work. In light of this observation, further research must be carried out to evaluate how nitrogen fixation conditions affect metabolic fluxes in A .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations